Clinical–epidemiological characteristics and survival time of deceased COVID-19 patients treated at hospitals belonging to Red Sabogal–Callao in 2020 - Llaro-Sánchez, Manuel K. (2020)
Objective: To describe the clinical–epidemiological characteristics and the survival time of deceased COVID-19 patients treated at hospitals belonging to Red Sabogal–Callao in 2020. Materials and methods: An observational, descriptive and retrospective study conducted in a population of 23 patients who died of COVID-19 from the beginning of the state of emergency (March 11, 2020) to April 15 at two hospitals belonging to Red Sabogal–Callao. The data was analyzed using the Stata Statistical Software: Release 16. The survival time was assessed by means of the Kaplan-Meier survival analysis and the log-rank test, with a 95 % confidence interval. Results: The predominant epidemiological characteristics were male sex, 60 to 79 years of age and comorbidities (hypertension and obesity). The main signs and symptoms at hospital admission were dyspnea, fever, cough and increased respiratory rate. Laboratory tests showed abnormal values: PaO₂/FiO₂ ratio < 300, leukocytosis, lymphopenia and increased lactate levels. Ground-glass opacities with bilateral pulmonary involvement prevailed in the radiological reports. During the hospital stay, 60.87 % of the patients were treated in the Intensive Care Unit (ICU), 69.57 % were on mechanical ventilation, 39.13 % received a therapeutic scheme consisting of hydroxychloroquine plus azithromycin, and 39.13 % received corticosteroids additionally to the aforementioned treatment. The patients died before reaching 20 days of hospital stay; on day five, the general survival probability was 43.48 %; and the survival probability was higher, although without statistical significance (p = 0.17), in those on mechanical ventilation. Conclusions: Deceased patients were mainly males, older adults, those with underlying health conditions such as hypertension and obesity, and those classified as having moderate to severe COVID-19 infection at hospital admission. The longest survival time was observed among those on mechanical ventilation.